Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.clinph.2018.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Finger strength, individuation, and their interaction: Relationship to hand function and corticospinal tract injury after stroke

Abstract: Multi-finger capacity may be an important target for rehabilitative hand training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 52 publications
(86 reference statements)
3
69
0
Order By: Relevance
“…[23][24][25][26][27][28] The degree of lesion to the CST was a key predictor of precision grip force control at 6 months after stroke, reflecting the essential role of CST for fine motor control, especially for precision grip performance and finger individuation. 9,12,29 CST lesion load was the only significant predictor of positive change in precision grip control from 3 weeks to 6 months post-stroke. 30,31 This suggests that neurobiological processes involving residual CST integrity are critical for recovery of fine motor control of fingers after stroke.…”
Section: Mechanism Underlying Impaired Precision Grip Force Controlmentioning
confidence: 90%
See 1 more Smart Citation
“…[23][24][25][26][27][28] The degree of lesion to the CST was a key predictor of precision grip force control at 6 months after stroke, reflecting the essential role of CST for fine motor control, especially for precision grip performance and finger individuation. 9,12,29 CST lesion load was the only significant predictor of positive change in precision grip control from 3 weeks to 6 months post-stroke. 30,31 This suggests that neurobiological processes involving residual CST integrity are critical for recovery of fine motor control of fingers after stroke.…”
Section: Mechanism Underlying Impaired Precision Grip Force Controlmentioning
confidence: 90%
“…The present study's second aim was to identify best predictors of both 6-month status and longitudinal recovery in precision grip force control after stroke. Based on previous reports, we hypothesized the strongest predictor would be the degree of lesion to the STROKE/2019/026205 R3 corticospinal tract (CST) 9,11,12 , but also that the best prediction model would additionally include measures of hand sensory 12,13 and motor impairment 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This hand function abnormality is thought to be a direct result of lesions to the motor cortex and corticospinal tract, 5,6,7,8,9 as these are known to be critical for the control of independent finger movements (i.e., finger individuation). 5,[10][11][12][13] Previously, we have shown that stroke patients recover both finger individuation and strength relying on separable recovery processes. 5 Recovery asymptotes after the first 3 to 6 months, although typically remains far from the level of performance of healthy individuals, especially for the individuation component.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic effect of the device has been demonstrated in the post-stroke rehabilitation training. To reflect the improvement of hand function, angle and torque of MCP and PIP joints are measured across each individual finger for examining the finger individuation (Wolbrecht et al, 2018), which is an important and comprehensive target for rehabilitative hand training. One major limitation of these robotic hands is shown in the bulkiness of mechanical linkages that translate finger movement to linear actuators, making them unsuitable for patients wearing them to perform activities of daily living (ADL).…”
Section: Introductionmentioning
confidence: 99%